Measuring Mobile Broadband Challenges and Implications for Policymaking - Zoraida Frias; William Lehr; Volker Stocker; Luis Mendo (International Telecommunications Society (ITS), 2023)
Mobile broadband networks constitute essential infrastructure to enable a wide range of innovative services and use cases anticipated for our digital economy future. Measuring performance is essential in many ways. First, to allow service providers to manage and develop their networks. Second, for the efficient operation of markets, and third, for evidence-based policymaking. In the rapidly evolving digital economy, capabilities for collecting more fine-grained measurements and analytics that deliver insights to enable real-time network management and localized control are expanding. As the fundamental methods used to collect measurement data are changing, the ecosystem of stakeholders with strategic interests in mobile measurement is growing and becoming more complex, posing challenges and opportunities for policymakers. Against the background of this growing complexity, this paper aims to discuss some basic features of a capable and reliable measurement ecosystem for mobile broadband. We document how the mobile broadband measurement ecosystem has changed and discuss its implications on a number of important broadband policy issues.
Keywords: 330; Mobile Broadband; Measurement; Performance; Evidence-based policymaking; Internet Policy; Telecommunications Policy